(untitled) (Biological Sciences - PJSIR, 2002)
Various l-aryl-pyrazole-4-carboxaldehyde benzylhydrazones were cyclized with polyphosphoric acid to give 5(1’ arylpyrazole-4’ -yl) 1,3,4-oxadiazoles (3-8) in good yields. Confimrntion of their structures was based on the results of elemental analyses, infrared and proton magnetic resonance spectra.